Intestinal Fut2 deficiency exacerbated alcohol‐related liver disease by disrupting nicotinamide metabolism - Liuying Chen; Zhongwei Yin; Luorui Shang; Hang Yuan; Wenkang Gao; Shuhan Wang; Shuyan Wang; Xiaohua Hou; Shenglan Yang; Huikuan Chu (Clinical and Translational Medicine)
Abstract Background Fucosyltransferase 2 (FUT2)‐dependent fucosylation of intestinal epithelial cells is vital for preserving gut barrier integrity and microbial balance. Nevertheless, its precise involvement in alcohol‐associated liver disease has yet to be fully elucidated. Methods We generated mice with intestinal epithelial cell‐specific Fut2 knockout (Fut2△IEC) and established a chronic‐binge alcohol model. 16S rRNA sequencing and metabolomics analysis were used to reveal differences in the composition and function of faecal bacteria. Results The loss of intestinal epithelial Fut2 exacerbates alcohol‐related hepatic oxidative stress damage, and this effect is dependent on gut bacteria. A marked decrease in the abundance of bacteria carrying nicotinamidase (PncA) in the intestines of Fut2△IEC mice was observed, leading to disrupted nicotinamide metabolism and decreased nicotinic acid production. This reduction in nicotinic acid synthesis results in decreased NAD+ production in the liver via the Preiss–Handler pathway. Administering pncA‐overexpressing Escherichia coli promotes hepatic NAD+ synthesis and alleviates alcohol‐related oxidative stress damage in Fut2△IEC mice. Conclusion These findings reveal a gut microbiota–Fut2–pncA axis that modulates alcoholic liver injury in mice, which may offer insights into microbial contributions to alcoholic liver disease in people. Key points Loss of intestinal epithelial fucosylation exacerbates alcohol‐related liver injuries. Intestinal epithelial deletion of Fut2 disrupts nicotinamide (NAM) metabolism due to the decline in bacterial nicotinamidase (PncA). Supplemented with pncA overexpressed E.coli to restore gut PncA levels can improve liver damage in alcohol‐induced intestinal epithelial Fut2 deletion mice.